The effectiveness of Tocotrienol rich fraction and αlpha Tocoferol with combination of vitamin C in the management of systemic inflammatory response syndrome (SIRS) - Husam YE; Raha Abdul Rahman; Jaafar MZ; Mohd Heikal Mohd Yunus (Pusat Perubatan Universiti Kebangsaan Malaysia, 2017)
The pathophysiology of systemic inflammatory response syndrome (SIRS) had been described to involve various strong oxidative reactions affecting the status and progress of the patients. Antioxidant therapy had been suggested in many studies involving SIRS management. The objective of this study was to compare the role of vitamin E Tocotrienol and vitamin E Tocopherol combined with vitamin C as antioxidant therapy in the management of critically ill patients diagnosed with SIRS, admitted to the intensive care unit and high dependency wards of Universiti Kebangsaan Malaysia Medical Centre (UKMMC). It was a single blind randomized clinical trial with a total of 72 patients in which 44.4% Malays, 34.7% Chinese, 19.4% Indians and 1.4% others with 59.7% males and 40.3% females were recruited. Patients in TRI E group received Tocotrienol with Vitamin C while TOCO group received Tocopherol with Vitamin C and a control group did not receive any antioxidant. The clinical parameters (heart rate, respiratory rate, systolic blood pressure) showed improvements with significant difference at the end of study (post-intervention) as compared to admission (pre-intervention).Whereas, the sepsis (temperature, PCT, CRP and WBC) and oxidative stress (8-OHdG/Creatinine) parameters showed improvements with significant difference at the end of study (post-intervention) as compared to admission (pre-intervention). The TRI E group showed obvious improvement in clinical, sepsis and oxidative stress parameters, as compared to TOCO and control groups. This study showed that Vitamin E Tocotrienol and Vitamin E Tocopherol in combination with Vitamin C demonstrated significant improvement in the clinical and laboratory parameters during the management of SIRS. Therefore, Vitamin E in combination with Vitamin C had therapeutic benefits in the treatment of critically ill patients with SIRS.